Prevalence of the Patterns of Unhealthy Diet in the School and University Students of Iran: A Systematic Review and Meta-Analysis - Seyyed Amir Yasin Ahmadi; Neda SoleimanvandiAzar; Mahshid Roohravan Benis; Ali Mehrabi; Roya Vesal Azad; Marzieh Nojomi (The Scientific World Journal)
Introduction. The present study was conducted to investigate the pooled prevalence rate of the different patterns of unhealthy diet among the school and university students of Iran. Methods. In this systematic review, the type of the main question was regarding prevalence and the effect measure was prevalence rate reported along with 95% confidence interval (CI). Data bases including PubMed, Scopus, and Web of Science as well as Google Scholar and Persian resources were used. The Newcastle–Ottawa scale (NOS) checklist was used for quality assessment of studies. Results. The extracted types of unhealthy diet in the present systematic review were “breakfast skipper,” “fast food,” “hydrogenated oils consumption,” “salty snacks,” “sweetened beverages,” “breakfast skipper,” “dinner skipper,” “launch skipper,” and “sweets.” The range of pooled prevalence for different types was 0.06–0.75. The data of 16,321 subjects included in six studies were analyzed. The pooled prevalence of unhealthy diet was 0.28 (95% CI: 0.23–0.33, I2 > 99%) overall, 0.25 (95% CI: 0.20–0.31, I2 > 99%) in school students and 0.37 (95% CI: 0.12–0.62, I2 > 99%) in university students. The most prevalent pattern was breakfast skipping 0.39 (95% CI: 0.28–0.50) followed by consumption of sweetened beverages 0.31 (95% CI: 0.20–0.43). The pooled prevalence range among the patterns was 0.06–0.75 (random effects for all). Conclusion. The pooled prevalence was 28% for unhealthy diet among the Iranian students (6% to 75% in different patterns). Although there was uncertainty regarding the pooled evidence, the whole of the mentioned range was clinically important for health policymakers. Decisions should be made on the basis of the patterns.